Gate‐Tunable van der Waals Photodiodes with an Ultrahigh Peak‐to‐Valley Current Ratio - Zubair, Muhammad; Wang, Hailu; Zhao, Qixiao; Kang, Mengyang; Xia, Mengjia; Luo, Min; Dong, Yi; Duan, Shikun; Dai, Fuxing; Wei, Wenrui; Li, Yunhai; Wang, Jinjin; et al. (Small (Weinheim an der Bergstrasse, Germany), 2023)
Photodetectors and imagers based on 2D layered materials are currently subject to a rapidly expanding application space, with an increasing demand for cost‐effective and lightweight devices. However, the underlying carrier transport across the 2D homo‐ or heterojunction channel driven by the external electric field, like a gate or drain bias, is still unclear. Here, a visible‐near infrared photodetector based on van der Waals stacked molybdenum telluride (MoTe2) and black phosphorus (BP) is reported. The type‐I and type‐II band alignment can be tuned by the gate and drain voltage combined showing a dynamic modulation of the conduction polarity and negative differential transconductance. The heterojunction devices show a good photoresponse to light illumination ranging from 520–2000 nm. The built‐in potential at the MoTe2/BP interface can efficiently separate photoexcited electron–hole pairs with a high responsivity of 290 mA W−1, an external quantum efficiency of 70%, and a fast photoresponse of 78 µs under zero bias. MoTe2/BP heterojunction photodiodes are demonstrated to show electrically‐tunable carrier transport and broadband photovoltaic performance. The device can realize a strong NDT behavior with a maximum PVCR of over 30. Assist with the built‐in potential, charge carriers can be efficiently separated, enabling a broadband photoresponse from 520 to 2000 nm, a high responsivity of 290 mA W‐1, and an EQE of 70%.